Sincering of value-at-risk models by incorporating the effect of market illiquidity: evidence on the Lima Stock Exchange - Indacochea Jáuregui, Silvana (2008)
Due to the high volatility and integration of emergent markets, the financial institutions have been obligated to make a more exact estimation of the potential losses in which they can incur as a consequence of negative markets scenarios. The most used tool to measure these possible potential losses is called Value at Risk (VaR). However, this indicator would underestimate the eventual potential losses if the asset presents low liquidity. Considering this financial context, the purpose of this research is: quantify the bias that suffers the risk models for investments portfolio, as they don’t take into consideration the liquidity risk adjustment. Having established this last point, the aim of the proposal will be to validate the hypothesis, in which the inclusion of a liquidity factor will vary significantly the risk models results, above the confidence intervals initially assumed for the Value at Risk analysis.In this sense, this research applies the liquidity adjusted VaR methodology to a number of Stock Exchange of Lima stocks, in order to incorporate the volatilities in the bid-ask spread of the assets. Finally, the obtained results demonstrate the real total risk of the assets as they incorporate the liquidity effect, reaching in some cases more than half of the total risk.